Making Blind Robots See: The Synergy Between Fluorescent Dyes and Imaging Devices in Automated Proteomics - Wayne F. Patton (BioTechniques)
Proteomics investigations endeavor to provide a global understanding of gene product synthesis rate, degradation rate, functional competence, posttranslational modification, subcellular distribution and physical interactions with other cell components. Protein expression encompasses an enormous dynamic range. Since rare proteins cannot be amplified by any type of PCR method, sensitive detection is critical to proteome projects. Fluorescence methods deliver streamlined detection protocols, superior detection sensitivity, broad linear dynamic range and excellent compatibility with modern microchemical identification methods such as mass spectrometry. Two general approaches to fluorescence detection of proteins are currently practiced: the covalent derivatization of proteins with fluorophores or noncovalent interaction of fluorophores either via the SDS micelle or through direct electrostatic interaction with proteins. One approach for quantifying fluorescence is to use a photomultiplier tube detector combined with a laser light scanner. In addition, fluorescence imaging is performed using a charge-coupled device camera combined with a UV light or xenon arc source. Fluorescent dyes with bimodal excitation spectra may be broadly implemented on a wide range of analytical imaging devices, permitting their widespread application to proteomics studies and incorporation into semiautomated analysis environments.